Student Perceptions of the Role of Tutors in Office Administration Courses in Public Administrastion Study Program of Universitas Terbuka - Sunarya, Amud (Yayasan Ilomata, 2024)
Whether a student is successful or not in undergoing lectures really depends on the role of the tutor in guiding the student. In this regard, the role of the tutor is very important because the tutor is a facilitator of learning for students. The problem currently occurring at the Universitas Terbuka is that there are many tutors who teach not in accordance with student expectations, such as not assessing discussions and assignments, not responding quickly to obstacles faced by students, not opening up discussion space and so on. For this reason, there needs to be a perception from students as a form of evaluation of the role of tutors in providing academic services to students so that they become quality graduates and can compete internationally. The aim of this research is to analyze student perceptions of the role of tutors in office administration courses as an effort to improve the quality of tutors' academic services to students. The research method used is quantitative. Research data was obtained directly from the field through a survey, namely by filling in a Google form. The selection of informants was based on purposive sampling. As for data analysis, researchers used interactive analysis. The research results show that students' perceptions of the role of tutors in Office Administration courses at the Universitas Terbuka are generally positive. The students assessed that the tutor was able to clearly convey the objectives and plans for learning activities, explain important concepts, and provide initiation materials equipped with supporting media such as video, audio or relevant articles. This shows that tutors play an important role in helping students understand the material and improving the quality of academic services, which ultimately supports students in competing on the international stage.